2008
DOI: 10.3846/1648-715x.2008.12.125-138
|View full text |Cite
|
Sign up to set email alerts
|

Hedonic Analysis of Price in the Istanbul Housing Market

Abstract: The purpose of this paper is to explore the factors that affect housing prices in Istanbul. A hedonic price model is employed in order to examine housing price determinants with respect to property characteristics, socio‐economic characteristics, neighbourhood quality characteristics, and locational factors. The results reveal that housing prices are affected by these factors: living area size, being in a low storey building, being in a secured site (with swimming pool and garage), and age of the building. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 21 publications
1
40
0
6
Order By: Relevance
“…This form was preferred to log-log and semi-log variants on the basis that it produced parameter estimates that were consistent with prior theory, a parsimonious equation that provided the best fit to the data and achieved the strongest performance on standard diagnostic tests. The superiority of the linear model over non-linear specifications is unusual but not unique (Keskin, 2008;Palmquist, 1984). The estimated parameters explain 61 per cent of the variation in house price levels which, although modest, falls within the normal range for reported hedonic models (Malpezzi, 2003).…”
Section: Resultsmentioning
confidence: 81%
“…This form was preferred to log-log and semi-log variants on the basis that it produced parameter estimates that were consistent with prior theory, a parsimonious equation that provided the best fit to the data and achieved the strongest performance on standard diagnostic tests. The superiority of the linear model over non-linear specifications is unusual but not unique (Keskin, 2008;Palmquist, 1984). The estimated parameters explain 61 per cent of the variation in house price levels which, although modest, falls within the normal range for reported hedonic models (Malpezzi, 2003).…”
Section: Resultsmentioning
confidence: 81%
“…Furthermore, variables such as the number of rooms, house size, availability of parking spaces and presence of ponds tended to have a price-increasing effect; however, being outside of the downtown area affected the price adversely. Keskin (2008) and Caglayan and Arikan (2009) both studied housing prices in Istanbul by taking the metropolitan area as a single market. Keskin, including socio-economic and neighborhood quality characteristics into her analysis, reported that the average income of the household, the length of time they lived in Istanbul and neighbor satisfaction increased the price while earthquake risk of the area decreased it.…”
mentioning
confidence: 99%
“…In the IMA, housing market is spatially segmented (Alkay 2008;Keskin 2008). Consequently, the changes in the market values seem to greater in the metropolitan area (Koramaz, Dökmeci 2012).…”
Section: General Characteristics Of the Housing Market In The Ima Andmentioning
confidence: 99%